"Flipped classrooms" in training in maxillofacial surgery: preparation before the traditional didactic lecture?. Issue 5 (June 2018) - Elledge, Ross; Houlton, Samantha; Hackett, Stephanie; Evans, Martin J.
Abstract: While virtual learning environments (VLE) can be used in medical education as stand-alone educational interventions, they can also be used in preparation for traditional "face-to-face" training sessions as part of a "flipped classroom" model. We sought to evaluate the introduction of this model in a single module on maxillofacial radiology from a course on trauma skills. Course delegates were randomised into two groups: one was given access to an e-learning resource (test group) and the other attended a traditional didactic lecture (control group). Knowledge and confidence were assessed before and after the course with a 20-question single-best-answer paper and a 10-situation 100 mm visual analogue scale (VAS) paper, respectively. All participants were then given free access to the VLE for 30 days and were invited to take part in an e-survey. Neither group showed improvements in the single-best-answer scores, but both groups showed comparable improvements in VAS (control: median (range) values improved from 40.8 (17.7–82.5) mm to 62.8 (35.3–88.7) mm, p = 0.001; test group: from 47.7 (10.9–58.1) mm to 60.5 (32.4–75.6) mm, p = 0.005). Half of the respondents stated that they preferred the "flipped classroom" approach, and 22/22 stated that they would be "likely" or "very likely" to use an e-learning resource with expanded content. The "flipped classroom" approach was well received and there were comparable improvements in confidence. As maxillofacial radiology lends itself to online instruction with its reliance on the recognition of patterns, and problem-based approach to learning, a piloted e-learning resource could be developed in this area.